SYSTEMATIC REVIEW OF SCIENTIFIC RESEARCH ON THE TRAINING OF FUTURE COMPUTER SCIENCE TEACHERS BASED ON STEAM EDUCATION - Maratova, Т.Ф.; Bostanov, Б.Г.; Kultan, Я.; Nauryzbayev, Д.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Today, STEM (science, technology, engineering and mathematics) education approaches are one of the new methods aimed at improving the digital and scientific literacy of the younger generation. In this regard, this article presents the results of a systematic review of effective research to determine the world-class application of the STEM education method in the process of identifying the main trends in the formation and training of future computer science teachers of a new direction. In particular, a systematic review of scientific articles published in Scopus in the unified bibliographic and abstract database of the world's peer-reviewed scientific literature over the past 5 years is presented in the course of determining the direction and effectiveness of the use of STEM educational opportunities along with traditional knowledge in the field of computer science. To determine it, a method of content analysis of article titles and summaries using keywords was carried out. As a result, the issues and directions of research development in the field of STEM education and computer science in the period from 2018 to 2022 in the scientific databases of Scopus were identified. The main purpose of this study is to identify the need to improve the methods of training future computer science teachers based on STEM education and lay the foundation for systematic mapping of research trends.